2010
DOI: 10.1021/ie100972h
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Isopropanol on Copper-Containing Mesoporous Catalysts

Abstract: Copper-containing mesoporous catalysts with an MCM-41 type structure have been prepared using direct hydrothermal synthesis and characterized using XRD, AAS, N 2 adsorption-desorption, DRUV-vis, and TEM. All of the samples showed high structural regularity and surface area. Three copper species are presented in these materials: isolated mononuclear Cu δ+ species, oligonuclear [Cuand bulky CuO oxides. These materials were catalytically tested in isopropanol dehydrogenation, showing good activity and very high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…Reflections shift toward lower • 2Â values with increases in the total metal content. This behavior has been previously associated with the inclusion of copper and palladium cations in the MCM-41 framework by Bálsamo et al [31] and Papp et al [34]. In the present work we observed that most of the Pd and Cu species during the template removal were present as oxides on the external surface of MCM-41 particles (see below).…”
Section: Catalyst Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Reflections shift toward lower • 2Â values with increases in the total metal content. This behavior has been previously associated with the inclusion of copper and palladium cations in the MCM-41 framework by Bálsamo et al [31] and Papp et al [34]. In the present work we observed that most of the Pd and Cu species during the template removal were present as oxides on the external surface of MCM-41 particles (see below).…”
Section: Catalyst Characterizationsupporting
confidence: 88%
“…DFT analysis confirms that the total volume adsorbed in the 4.3 nm mesopores is lower in comparison to other samples, and that 6-7 nm pores are also present in this sample. The presence of large copper and palladium oxide particles may be responsible for the change in the sample textural properties [31,34].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…27, 33 In addition, very broad peak at above 400 nm is assigned to pseudo-octohedral ligand oxygen 10 environment of copper. 17,18,23,24,33 Among the three samples, CuTA showed an intense absorption peak at 310 nm, which indicate of presence of oligonuclear CuO clusters 18 and also an indirect evidence for lesser incorporation of Cu 2+ into the silica matrix. Furthermore, for all the CuTUD-1 samples a relative 15 percentage of Cu species were estimated from the respective absorption peak areas.…”
Section: Catalyst Characterizationmentioning
confidence: 97%
“…12 Though the high content of divalent metal ions such as Cu 2+ are difficult to incorporate into the 50 mesoporous silica, many research groups have devoted to pack the Cu 2+ sites as complex or direct incorporation into silica framework. [13][14][15][16][17][18] It has been well known that one of the important factor that determines the dispersion of Cu 2+ active site which are in turn influenced in the direct synthesis method by structural 55 nature of copper precursors, coordinative environment, rate of hydrolysis and solubility. Hence, the selection of copper source is of prime concern in the copper based mesoporous material synthesis.…”
Section: Introductionmentioning
confidence: 99%